Anna and the King [videorecording (DVD)] - Leonowens, Anna Harriette, 1831-1915 (20th Century Fox Home Entertainment, 2000)
English schoolteacher Anna Leonowens has traveled to Siam to educate the 58 children of King Mongkut. Each has preconceived ideas about the other's world. Amid the danger of political unrest, their respect for each other turns into something more.